Effective strategies to realize high-performance graphene-reinforced cement composites. (21st March 2022) - Basquiroto de Souza, Felipe; Yao, Xupei; Lin, Junlin; Naseem, Zunaira; Tang, Zhao Qing; Hu, Yaoxin; Gao, Wenchao; Sagoe-Crentsil, Kwesi; Duan, Wenhui
Highlights: Novel strategies to effectively incorporate GNS into cement materials were reviewed. The performance of GNS-reinforced cement materials was analytically covered. Directions to develop a scientific understanding of GNS–cement materials were presented. Recommendations to further explore the potentials of GNS in cement materials were given. Abstract: Owing to their remarkable properties, graphene-based nanosheets (GNS) can enable the fabrication of high-performance and sustainable cement composites. Here we review recent advances in GNS-reinforced cementitious composites, focused on the novel strategies (i.e., dispersion, hybridization, coating, and dry mixing approaches) to effectively incorporate GNS into cement/concrete mixes. Furthermore, the impacts of GNS-reinforcement on the mechanical, durability and functional performance of cementitious materials were analytically covered. Lastly, we highlighted the increasing understanding of the fundamentals of the distribution and interplay of GNS within the complex cement microstructure – towards scientific principles to confidently translate GNS to the construction industry.